Spermidine exogenous application mollifies reproductive stage heat stress ramifications in rice - Karwa, Sourabh; Taunk, Jyoti; Maurya, Sadhana; Das, Adhip; Krishna, G. K.; Arya, Sunder Singh; Kumar, Awadhesh; Kumar, Sudhir; Kumar, Pramod; Chinnusamy, Viswanathan; Pal, Madan (Frontiers in Plant Science, 2022)
Rice productivity is severely hampered by heat stress (HS) which induces oxidative stress in this crop. This oxidative stress can be alleviated using various exogenous chemicals, including spermidine (Spd). Therefore, the present study was carried out to characterize HS components and to elucidate the role of exogenous Spd application in rice at the flowering stage. Two contrasting rice genotypes, i.e., Nagina22 (N22) and Pusa Basmati-1121 (PB-1121), were placed in temperature tunnels and exposed to HS (38–43°C) with and without Spd (1.5 mM) foliar application during the heading stage till the end of the anthesis stage. Heat stress induced the production of H2O2 and thiobarbituric acid reactive substances, which resulted in lower photosynthesis, spikelet sterility, and reduced grain yield. Interestingly, foliar application of Spd induced antioxidant enzyme activities and thus increased total antioxidant capacity resulting in higher photosynthesis, spikelet fertility, and improved grain yield under HS in both genotypes. Under HS with Spd, higher sugar content was recorded as compared to HS alone, which maintained the osmotic equilibrium in leaf and spikelets. Spd application initiated in vivo polyamine biosynthesis, which increased endogenous polyamine levels. This study corroborates that the exogenous application of Spd is promising in induction of antioxidant defence and ameliorating HS tolerance in rice via improved photosynthesis and transpiration. Thereby, the study proposes the potential application of Spd to reduce HS in rice under current global warming scenario.